Histone deactylase gene expression profiles are associated with outcomes in blunt trauma patients. Issue 1 (January 2016) - Sillesen, Martin; Bambakidis, Ted; Dekker, Simone E.; Fabricius, Rasmus; Svenningsen, Peter; Bruhn, Peter James; Svendsen, Lars Bo; Hillingsø, Jens; Alam, Hasan B.
Abstract : BACKGROUND: Treatment with histone deacetylase (HDAC) inhibitors, such as valproic acid, increases survival in animal models of trauma and sepsis. Valproic acid is a pan-inhibitor that blocks most of the known HDAC isoforms. Targeting individual HDAC isoforms may increase survival and reduce complications, but little is known of the natural history of HDAC gene expression following trauma. We hypothesized that distinct HDAC isoform gene expression patterns would be associated with differences in outcomes following trauma. METHODS: Twenty-eight–day longitudinal HDAC leukocyte gene expression profiles in 172 blunt trauma patients were extracted from the Inflammation and the Host Response to Injury (Glue Grant) data set. Outcome was classified as complicated (death or no recovery by Day 28, n = 51) or uncomplicated (n = 121). Mixed modeling was used to compare the HDAC expression trajectories between the groups, corrected for Injury Severity Score (ISS), base deficit, and volume of blood products transfused during the initial 12 hours following admission. Weighted gene correlation network analysis identified modules of genes with significant coexpression, and HDAC genes were mapped to these modules. Biologic function of these modules was investigated using the Gene Ontology database. RESULTS: Elevated longitudinal HDAC expression trajectories for HDAC1, HDAC3, HDAC6, and HDAC11 were associated with complicated outcomes. In contrast, suppressed expression of Sirtuin 3 (SIRT3) was associated with adverse outcome ( p < 0.01). Weighted gene correlation network analysis identified significant coexpression of HDAC and SIRT genes with genes involved in ribosomal function and down-regulation of protein translation in response to stress (HDAC1), T-cell signaling, and T-cell selection (HDAC3) as well as coagulation and hemostasis (SIRT3). No coexpression of HDAC11 was identified. CONCLUSION: Expression trajectories of HDAC1, HDAC3, HDAC6, HDAC11, and SIRT3 correlate with outcomes following trauma and may potentially serve as biomarkers. They may also be promising targets for pharmacologic intervention. The effects of HDAC and SIRT gene expression in trauma may be mediated through pathways involved in ribosomal and T-cell function as well as coagulation and hemostasis. LEVEL OF EVIDENCE: Prognostic study, level III.